Desiminasi inovasi dan pengembangan jejaring kemitraan pada kelompok usaha kripik talas untuk membangun desa wisata (Desa Tambakmerang Kecamatan Girimarto Kabupaten Wonogiri) - Agung Wibowo; Eny Lestari; Eksa Rusdiana (Unri Conference Series: Community Engagement, 2020)
Productive economy and creative economy serve as the basis for developing tourist villages. The development of a tourism village needs to pay attention to the local wisdom contained in the location, this aims to show the identity of the tourist village and show its own uniqueness that can be used to differentiate it from tourist villages in other places. The main problem faced by MSME actors in Tambakmerang Village is marketing which can only reach around the area within one sub-district and sub-district nearby. The PKM (Community Partnership Program) team facilitates the introduction of their products by introducing web site technology and social media so that MSME actors can be widely known. Furthermore, the PKM team will also conduct training and mentoring to support online sales. In order to carry out the Community Partnership Program for Taro Chips craftsmen, it is carried out by combining various methods including: socialization and training, mentoring, Optimizing efficient technology transfer, and Optimizing the use of information technology. Technically, there are several activities of this Community Partnership Program, which are as follows: (1) introducing appropriate technology and training; (2) facilitating cooperation between MSME actors in Tambakmerang Village, (2) facilitating web sites and social media to introduce them to the public; (3) developing institutional capacity.